2022
DOI: 10.1111/jgh.15878
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating diagnostic performance of Truenat MTB Plus for gastrointestinal tuberculosis

Abstract: Background and Aim Prompt and accurate diagnosis of gastrointestinal tuberculosis (GITB) along with simultaneous detection of drug resistance is inevitable for tuberculosis elimination. Truenat MTB Plus (TruPlus), a chip‐based real‐time polymerase chain reaction assay, was evaluated for the first time for diagnosing GITB and detecting rifampicin resistance. Methods Fifty ileocecal biopsy specimens (5 microbiologically confirmed GITB [culture‐positive], 25 clinically confirmed GITB [culture‐negative], and 20 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The NAATs provide an opportunity for reliable diagnosis of GITB by amplification and detection of DNA of M. tuberculosis . The ileocecal biopsy was used as the sample in the current study as this site is involved in 64% of GITB cases 20 and has reported highest bacillary yield in previous studies, 14 because of lymphoid aggregates, minimal activity, and neutralized digestive secretions 21 . MTBDRplus and MTBDRsl assays, with their ability to detect both first‐line and second‐line drug resistance simultaneously, could serve as beacons of hope for TB elimination 2,22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NAATs provide an opportunity for reliable diagnosis of GITB by amplification and detection of DNA of M. tuberculosis . The ileocecal biopsy was used as the sample in the current study as this site is involved in 64% of GITB cases 20 and has reported highest bacillary yield in previous studies, 14 because of lymphoid aggregates, minimal activity, and neutralized digestive secretions 21 . MTBDRplus and MTBDRsl assays, with their ability to detect both first‐line and second‐line drug resistance simultaneously, could serve as beacons of hope for TB elimination 2,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Overcoming the limitations of conventional microbiological tests, a variety of nucleic acid amplification tests (NAATs) have been used for diagnosing GITB (multiplex polymerase chain reaction, 12 loop‐mediated isothermal assay, 13 etc.) and also for detecting DR‐GITB (GeneXpert and Truenat) 14 . While GeneXpert is limited to detection of Rif resistance only, Truenat allows detection of MDR, pre‐XDR, and XDR, albeit using separate amplification chips for each.…”
Section: Introductionmentioning
confidence: 99%
“…No reports are available on the utility of newer PCR-based diagnostics such as Xpert Ultra. One study has reported that the sensitivity and specificity of Truenat MTB Plus (TruPlus) were 70% and 100%, respectively [58]. As with peritoneal tuberculosis, multiplex PCR based on multiple probes has been found to be sensitive and specific but needs validation [52,58].…”
Section: Microbiologymentioning
confidence: 99%
“…However, there is limited data on the Truenat’s utility in diagnosing EPTB especially from India. Studies from Chandigarh documented a sensitivity of 66.6% and 70% in Truenat testing of vitreous fluid and ileocecal biopsy specimens respectively [6] , [7] . A study from Kerala that tested different extrapulmonary specimens demonstrated 100% sensitivity of Truenat testing for M.tuberculosis diagnosis [8] .…”
Section: Introductionmentioning
confidence: 99%